Cyanobacteria biofertilizer solubilizes soil phosphorus and alters soil microbial communities - Afkairin, Antisar, author; Davis, Jessica G., advisor; Stromberger, Mary E., committee member; Storteboom, Heather, committee member; Weir, Tiffany, committee member (Colorado State University. Libraries, 2022)
To view the abstract, please see the full text of the document.